From Growth Mindset and Social Media Influence to Learning Outcomes: A PLS-SEM Study in Indonesian Higher Education - Andika Isma; Andi Naila Quin Azsisah Alisyahbana; Sahabuddin Sahabuddin; Akhmad Khairul Shiddiq; Della Fadhilatunisa (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
This study examines how growth mindsets and social media influence shape learning outcomes through student engagement and digital literacy in digitally mediated higher education. Survey data were collected from 478 undergraduate students enrolled at higher education institutions in Indonesia and analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4. The measurement model demonstrated satisfactory reliability, convergent validity, and discriminant validity. The structural model explained 67.3% of the variance in learning outcomes, 60.5% in student engagement, and 40.7% in digital literacy, indicating a substantial explanatory power. Growth mindset positively predicted learning outcomes, student engagement, and digital literacy, with the strongest substantive effect observed on student engagement. Social media influence positively predicted student engagement and digital literacy but did not have a significant direct effect on the learning outcomes. Student engagement and digital literacy both positively predicted learning outcomes, and indirect-effect analysis confirmed several mediating pathways linking growth mindset and social media influence to learning outcomes. These findings indicate that the academic benefits of digital higher education are not produced by mindset or social media exposure alone. Learning outcomes improve when psychological dispositions and social-digital interactions are translated into active engagement and effective digital literacy.